1 GASTROESOPHAGEAL REFLUX DISORDER: HIGH ADRENERGIC NEUROVASCULAR TONE WITH HIGH VAGAL TONE. (1st March 2006) - Abdelmelek, O.; Barndt, R.; Mina, N.; Iskarous, J.; Huang, J.
Abstract : Severe gastroesophageal reflux disorder (GERD) is poorly understood, precluding prevention therapy (Rx). Our pilot study (PS) shows that increases in adrenergic neurovascular (ANVT) and vagal tone (VT) cause severe GERD and reduction in ANVT decreases symptom levels (SL). Prospective studies (ProS) were done with a random sample of the general population with severe GERD as in PS. Severe GERD (reflux to pharynx) correlated with the following PS criteria: rise in pulse pressure (RPP) > 15 mm Hg (during handgrip at 5 psi/3min), systolic time intervals (STI) < 31% (24-30%), and resting heart rate (HR) at 60 ± 5 (predicts high VT). Serial measurements were made at time 1 and 2 (T1/2 = before/during 1 year Rx). Serial measurements were made of STI, HR10AM (HRA, peak ANVT), HR 12 noon (HRN, peak VT), % change in HR 10 am-12 noon (%CHR), systolic blood pressure (SBP), cardiac output (CO), systemic vascular resistance (SVR), and symptom levels (SL 1-100). Patients were 3/1 females/males, 18-70 years of age, all Caucasian. Exclusions were other gastric problems, fibromyalgia, diabetes, hypertension, and on other drugs. Controls (C) were normal, sex/age/race matched. Rx: diltiazem CD 240-360 mg/day, methyldopa 125-500 mg/day, and amitriptyline 10-100 mg/day, with double-blind crossover design. All data were placed into a blind matrix for analysis later. Severe GERD was predicted by STI of 24-30% by PS findings. Results: G means shown: ProS results confirm PS results showing that severe GERD was found in people with high ANVT, during a shift to high vagal tone, with Sig reduction in HR from peak ANVT at 10 am to peak VT at 12 noon. Basilar artery migraine was also found in 95% of ProS patients with high ANVT and high vagal tone. SL of ProsS patients were significantly reduced by Rx. Thus, GERD is due to high ANVT with increased vagal tone and can be prevented with therapy.